2014
DOI: 10.5901/mjss.2014.v5n6p179
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Confronting the Quality of Postgraduate Research Supervision and Its Effects on Time-to-Degree and Throughput Rates: A Case of a South African University

Abstract: Quality of academic research supervision is one of the major determinants of time-to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The results revealed that research supervision significantly contributes to the graduate students' progress in public higher institutions of learning. These findings are in alignment with the findings of the previous studies (Chiappetta-Swanson & Watt, 2011;Chireshe, 2012;Holtman & Mukwada, 2014;Van Rensburg, Mayers & Roets, 2016;Akparep, Jengre & Amoah, 2017) that highlight research supervision as a major factor that explains the graduate students' completion and retention rate.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…The results revealed that research supervision significantly contributes to the graduate students' progress in public higher institutions of learning. These findings are in alignment with the findings of the previous studies (Chiappetta-Swanson & Watt, 2011;Chireshe, 2012;Holtman & Mukwada, 2014;Van Rensburg, Mayers & Roets, 2016;Akparep, Jengre & Amoah, 2017) that highlight research supervision as a major factor that explains the graduate students' completion and retention rate.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
“…The existing literature reveals that research supervision as a critical factor that improves the completion time and attrition rates for university courses where a research project is a requirement (Chiappetta-Swanson & Watt, 2011;Chireshe, 2012;Holtman & Mukwada, 2014;Van Rensburg, Mayers & Roets, 2016;Akparep, Jengre & Amoah, 2017). According to Chiappetta-Swanson and Watt (2011), research supervision can only contribute to the progress of the graduate students when the supervisors provide adequate support and guidance during the research process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome also indicates that students are likely to have problems of conducting useful scientific research which might be the reason students are having challenges in postgraduate studies across the globe (Holtman & Mukwada, 2014;Oni, Onyenania, & Momoh, 2017;Talebloo & Baki, 2013). To be successful in postgraduate studies in universities requires that students must be able to conduct a research study independently with little or no supervision.…”
Section: Discussionmentioning
confidence: 99%